A metering network for a smart prepaid scheme under an electrical utility organization - Rahman, Md. Ashrafur; Roy, Tridib; Saiara, Syeda Afra; Mubassir, Sheikh Tajnur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.